Minor Chemistry Changes Alter Surface Hydration to Control Fibronectin Adsorption and Assembly into Nanofibrils. Issue 12 (28th October 2019) - Bieniek, Mateusz K.; Llopis‐Hernandez, Virginia; Douglas, Katie; Salmeron‐Sanchez, Manuel; Lorenz, Christian D.
Abstract: Fibronectin (FN) is a large glycoprotein which links and transmits signals between the cell's cytoskeleton and the extracellular matrix. FN organization into fibrils and then fibrillogenesis can be induced with the right substrate, such as poly(ethyl acrylate) (PEA), on which FN becomes extended. Interestingly, the almost identical polymer poly(methyl acrylate) (PMA), which has one less methylene bridge (─CH2 ─), does not cause fibrillogenesis. To investigate the difference in FN behavior on PEA and PMA, the two substrates are modeled using ethyl acrylate (EA) and methyl acrylate (MA) functionalized self‐assembled monolayers (SAMs). It is confirmed experimentally that the EA and MA SAMs exhibit a similar behavior in vitro to the polymers in terms of fibronectin fibrillogenesis, domain exposure, and cell adhesion. All‐atom molecular dynamics simulations of the FNIII 9‐10 domains interacting with each SAM show the adsorption of these two domains on EA SAMs and no adsorption on MA SAMs. Consistently, the experiments show that FN fibrillogenesis takes place on EA SAMs but not on MA SAMs. It is found that the extra methylene group in the EA headgroup leads to more motion within the headgroup that results in a markedly less dense hydration layer, which facilitates FN fibrillogenesis. Abstract : A combination of experimental and simulation investigations is used to understand the molecular interactions that result in the material‐driven fibrillogenesis of fibronectin on ethyl acrylate functionalized self‐assembled monolayers (SAMs), which isn't observed when fibronectin adsorbs to methyl acrylate functionalized SAMs. The interfacial water structure at the two interfaces is found to be key to the difference in adsorption of fibronectin.